Isoflavones - Křížová, Ludmila; Dadáková, Kateřina; Kašparovská, Jitka; Kašparovský, Tomáš (Molecules (Basel, Switzerland), 2019)
Phytoestrogens are naturally occurring nonsteroidal phenolic plant compounds that, due to their molecular structure and size, resemble vertebrate steroids estrogens. This review is focused on plant flavonoids isoflavones, which are ranked among the most estrogenic compounds. The main dietary sources of isoflavones for humans are soybean and soybean products, which contain mainly daidzein and genistein. When they are consumed, they exert estrogenic and/or antiestrogenic effects. Isoflavones are considered chemoprotective and can be used as an alternative therapy for a wide range of hormonal disorders, including several cancer types, namely breast cancer and prostate cancer, cardiovascular diseases, osteoporosis, or menopausal symptoms. On the other hand, isoflavones may also be considered endocrine disruptors with possible negative influences on the state of health in a certain part of the population or on the environment. This review deals with isoflavone classification, structure, and occurrence, with their metabolism, biological, and health effects in humans and animals, and with their utilization and potential risks.
Keywords: Equol; Phytoestrogens; biochanin A; isoflavony; Animals; glycitein; fytoestrogeny; phytoestrogens; zvířata; Humans; Isoflavones; daidzein; formononetin; Genistein; equol; isoflavones; lidé; genistein